Celestial Mechanics and the Location Theory of William H. Dean, Jr., 1930-52 - Ellison, Julian (American Economic Review, 1991)
William Henry Dean, Jr. was born in 1910 and died in 1952. He was the only son, and third of four children, of Reverend William Henry Dean and the former Ella Cornelia Green. His father was a Methodist minister, and the family lived in the cities in which he pastored churches: Lynchburg, VA; Washington, D.C.; Baltimore, MD; and Pittsburgh, PA. The son graduated from Frederick Douglass High School in Baltimore in 1926 as valedictorian of his class. He attended Bowdoin College in Maine, graduating summa cum laude in 1930. He then entered Harvard University, where he earned the M.A. and the Ph.D. in economics in 1932 and 1938, respectively. His subsequent career included stays with Atlanta University, 1933-42; City College of New York, summer 1939; U.S. National Resources Planning Board, 1940-42; U.S. Office of Price Administration, Virgin Islands, 1942-44; National Urban League, 1944-46; and United Nations, 1946-52 (Rayford Logan and Michael Winston, 1982). This paper examines briefly the sources of location theory in the mathematics and astronomy of the day, and Dean's application of results from these fields to economic location theory in his doctoral dissertation at Harvard University in 1938.